Urgensi Manajemen Risiko dalam Bidang Pendidikan - Marcha Juliadrianti; Irsyad, Irsyad; Merika Setiawati (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
Risk management in education plays a crucial role in maintaining safety, stability, and sustainability in the learning process. This study aims to explore the urgency, strategies, and best practices of risk management in educational institutions at various levels. The research method employed is a literature review, which analyzes relevant sources such as books, journals, and academic articles discussing the implementation of risk management in education. The findings indicate that effective risk management involves a systematic process of identifying, analyzing, mitigating, and monitoring risks. Furthermore, collaboration among teachers, students, parents, and administrators is essential to establish a risk-aware culture within educational institutions. Proactive implementation of risk management not only enhances operational effectiveness and financial efficiency but also strengthens institutional reputation and ensures the continuity of quality education. The study provides strategic insights that can guide educational stakeholders in developing adaptive and sustainable risk management frameworks.